Proclamation, Toussaint Louverture : général en chef, de l'armée de Saint-Domingue, à ses concitoyens de la ville du Cap, aux militaires de sa garnison et aux cultivateurs de la Plaine - Toussaint Louverture, 1743-1803 (Chez P. Roux, imprimeur de la Commission, 1797)
May of 1797 had seen Julien Raimond and Sonthonax, the commiassaires of Saint-Domingue, name Toussaint Louverture to the post of chief of the French army in Saint-Domingue. On August 25th, Sonthonax departed from Saint-Domingue to return to France. Toussaint here asks for order to be kept, for the planting and cultivation to continue as normal and asks his countrymen to have confidence in the government and their desire to restore order to the colony and glory to the colony.